Vulnerability of identity and memory Jasenovac, Ricoeur, and the death of God - Mladenovska-Tešija, Julijana; Đukić, Luka, student teologije; Edelinski, Davor (2018)
This paper was created as a result of discussions with the students from the Evangelical Theological Seminary in Osijek, as part of the Introduction into Philosophy course. In the paper we used parts of Luka Đukić’s essay, “Memorial Centers: The Role of Memory,” which have, as part of dialogue regarding the role of memory, been inserted into the text by J. Mladenovska-Tešija. The purpose of the paper is to emphasize the relevance of Ricoeur’s reflections about memory for Evangelical Christians, especially considering Christ’s death on Calvary as an anti-narrative.
Ovaj je rad nastao kao rezultat diskusija koje su se vodile sa studentima Visokoga evanđeoskoga teološkog učilišta u Osijeku, u okviru kolegija Uvod u filozofiju. U radu su korišteni dijelovi eseja studenta Luke Đukića “Memorijalni centri: uloga pamćenja” koji su, u cilju dijaloga o ulozi pamćenja, umetnuti unutar teksta J. Mladenovske-Tešije. Cilj je rada ukazati na relevantnost Ricoeurova razmišljanja o pamćenju za evanđeoske kršćane, posebice imajući u vidu Kristovu smrti na Golgoti kao protunarativ.
Bibliografija: 17 jed.
Summary ; Sažetak.
Keywords: Identitet -- Pamćenje -- Trauma -- Uskrsnuće; Isus Krist -- Ricoeur, Paul